Step
*
of Lemma
satisfies-shadow-inequalities
No Annotations
∀[n:ℕ]. ∀[ineqs:{L:ℤ List| ||L|| = n ∈ ℤ}  List]. ∀[i:ℕ+n]. ∀[xs:ℤ List].
  (∀as∈shadow-inequalities(i;ineqs).xs\i ⋅ as ≥0) supposing (∀as∈ineqs.xs ⋅ as ≥0)
BY
{ (Auto THEN Assert ⌜∀L:ℤ List. ((L ∈ ineqs) 
⇒ i < ||L||)⌝⋅) }
1
.....assertion..... 
1. n : ℕ
2. ineqs : {L:ℤ List| ||L|| = n ∈ ℤ}  List
3. i : ℕ+n
4. xs : ℤ List
5. (∀as∈ineqs.xs ⋅ as ≥0)
⊢ ∀L:ℤ List. ((L ∈ ineqs) 
⇒ i < ||L||)
2
1. n : ℕ
2. ineqs : {L:ℤ List| ||L|| = n ∈ ℤ}  List
3. i : ℕ+n
4. xs : ℤ List
5. (∀as∈ineqs.xs ⋅ as ≥0)
6. ∀L:ℤ List. ((L ∈ ineqs) 
⇒ i < ||L||)
⊢ (∀as∈shadow-inequalities(i;ineqs).xs\i ⋅ as ≥0)
Latex:
Latex:
No  Annotations
\mforall{}[n:\mBbbN{}].  \mforall{}[ineqs:\{L:\mBbbZ{}  List|  ||L||  =  n\}    List].  \mforall{}[i:\mBbbN{}\msupplus{}n].  \mforall{}[xs:\mBbbZ{}  List].
    (\mforall{}as\mmember{}shadow-inequalities(i;ineqs).xs\mbackslash{}i  \mcdot{}  as  \mgeq{}0)  supposing  (\mforall{}as\mmember{}ineqs.xs  \mcdot{}  as  \mgeq{}0)
By
Latex:
(Auto  THEN  Assert  \mkleeneopen{}\mforall{}L:\mBbbZ{}  List.  ((L  \mmember{}  ineqs)  {}\mRightarrow{}  i  <  ||L||)\mkleeneclose{}\mcdot{})
Home
Index